A STUDY ON SILICA SAND QUALITY IN YAZARAM AND MUGULBU DEPOSITS FOR GLASS MAKING (Nigerian Journal of Technology, 2014)
The suitability of silica sand deposits of Yazaram and Mugulbu in Mubi South Local Government Area of Adamawa State, Nigeria for commercial glass production were assessed based on the chemical and physical properties of the silica sand samples collected along the river side’s. Test was carried out at the National Metallurgical Development Centre (NMDC), Jos. The chemical analysis was carried out using X-ray florescence spectrometer (XRFS) and the physical properties such as the particle size, grain morphology and the specific gravity examinations were carried out using mechanical shaker (sieving method), electronic microscope to reveal the shape of the samples and the specific gravity testing machine respectively. The results obtained were assessed and compared with the standard requirements for glass making.  Mugulbu had the highest percentage of silica content of 77.70% and Yazaram had the lowest percentage of silica content of 77.60% and the grain morphology was found to be angular with specific gravity of 2.50 for both the samples, which were found to be within the acceptable limits for glass making.  The iron oxide content in all the samples was found to be high, with highest value of 1.94% for Mugulbu and lowest value of 1.05% for Yazaram.  However, the iron content for all the samples was above 1% thereby limiting the range of applications to coloured and amber glass manufacturing.  The physical properties for all the samples were found to satisfy the standard requirements for glass making. http://dx.doi.org/10.4314/njt.v34i1.13